Preparation of Epigallocatechin Gallate-Enriched Antioxidant Edible Films Based on Konjac Glucomannan and Sodium Alginate: Impact on Storage Stability of Mandarin Fish - Ran Wang; Yuqi Wang; Xinzhen Zhang; Yang Gao; Xian Wu; Xueling Li; Zhengquan Liu; Yue Sun; Jin Liang (Foods)
The objective of this research was to prepare robust edible films possessing antioxidant properties by utilizing konjac glucomannan (KGM), sodium alginate (SA), and epigallocatechin gallate (EGCG). This research also involved structural characterization and the assessment of functional attributes of the composite films with varying EGCG concentrations. It was found that the inclusion of EGCG reduced the viscosity of the edible film solutions while enhancing their mechanical strength. Fourier transform infrared spectroscopy demonstrated adequate compatibility among the film-forming materials, with EGCG forming hydrogen bond interactions with KGM and SA. SEM analysis revealed that increasing EGCG concentration led to the formation of discontinuous blocks and rough surfaces, with smooth and fine-grained particles observed at 0.2% (w/v) EGCG concentration. Furthermore, results from the application of the KGM-SA-based films in chilled mandarin fish showed that they could exert antioxidant function when incorporated with EGCG. The values of TVB-N and TBARS of fish pieces were obviously decreased in the 12-day storage period, indicating their potential to increase the shelf life of freshwater fish food.